The Interaction of Dried Distillers Grains With Solubles (DDGS) Type and Level on Growth Performance, Health, Texture, and Muscle-Related Gene Expression in Grass Carp (Ctenopharyngodon idellus) - Abouel Azm, Fatma Ragab; Kong, Fanshuang; Wang, Xiaoyu; Zhu, Wenhuan; Yu, Haojie; Long, Xianmei; Tan, Qingsong (Frontiers in Nutrition, 2022)
The aim of this study was to estimate the possible synergetic effects of the two levels of dietary dried distillers grains with solubles (DDGS) from different sources (US-imported and native) on the growth, health status, muscle texture, and muscle growth-related gene expression of juvenile grass carp. Four treatments of fish were fed with 4 isonitrogenous diets, namely, native DDGS20, native DDGS30, US-imported DDGS20, and US-imported DDGS30 for 60 days. The US-imported DDGS30 group showed the better growth and feed efficiency. Additionally, we observed a significant increase in hepatopancreatic total antioxidant capacity (T-AOC) and superoxide dismutase (SOD) in native DDGS groups. Moreover, raw muscle collagen increases considerably in the US-imported DDGS30 compared with the native DDGS30 group. In comparison with the native DDGS groups, the US-imported DDGS groups showed significantly decrease in all textural properties and fiber density, while increased fiber diameter. Dietary native DDGS inclusion significantly showed the upregulation of myog, myhc, and fgf6a expression in muscle, while the downregulation of the expression of myod and myf5. Overall, US-imported DDGS30 had a beneficial influence on growth via regulating genes involved in myogenesis and hypertrophy, the formation of collagen, but had negative impacts on antioxidant capacity and cooked muscle texture.